Validity and Reliability Tests of Ahmad Dahlan Linguistic Test (ADLT) - Puspitasari, Intan; Hidayat, Muhammad; Khasanah, Ramadhani Uswatun; Kahraman, Özlem Gözün (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2024)
Language development assessment tools for early childhood currently often refer to the Developmental Milestones Standards for Children (STPPA), based on core competencies and basics in the 2013 Early Childhood Education curriculum. These standards are used as references for development to ensure age-appropriate play activities for children. However, language development assessment tools for broader use still require further development to effectively identify children's language development. The aim of this study was to develop a language development assessment tool for early childhood, focusing on phonetics, semantics, and syntax according to Otto's theory (2015), to enable early detection of language delays in children. The researchers conducted three stages, including tool development, validation by experts, and testing on a limited sample. Although the tool was validated by five professors with Aiken's V scores > 0.8 and an overall reliability of 0.739, the semantic aspect was found to be unreliable (Cronbach Alpha < 0.7). Therefore, while the Early Language Detection Tool (ADLT) is considered valid and reliable, it still requires further adjustment to better suit the context of early childhood.